PENERAPAN INTEGRATED FARMING SEBAGAI STRATEGI PENINGKATAN PENDAPATAN PADA KELOMPOK WANITA TANI INDAH SARI KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Triani, Hera Dwi; Harly, Resolinda; Elmiati, Reni; Amri, M.; Indra, Ristapawa; Yanti, Gusri; Etikushera, Etikushera; Yolanda, Tasya (LPPM Universitas Andalas, 2024)
The objective of this activity is to implement integrated farming in agriculture and livestock to enhance efficiency, food security, and household income. The partner's main production challenges include low productivity in agriculture and livestock, caused by the high cost of fertilizers, pesticides, and livestock feed. Economically, the partner struggles with low income due to high production costs and limited productivity, which negatively impacts family welfare. Additionally, environmental pollution caused by accumulated agricultural and livestock waste poses a significant issue. The implementation methods involved socialization of integrated farming benefits, training on compost production, liquid organic fertilizer (LOF), and pesticide processing from livestock waste, as well as feed processing from agricultural waste through cassava peel fermentation. Following the training, compost, LOF, and pesticides were applied to horticultural crops, and fermented feed was utilized for livestock. The outcomes of this activity include the successful conversion of livestock waste into compost, LOF, and biopesticides, as well as cassava peel waste into high-quality feed. Compost, LOF, and biopesticides have been applied to horticultural crops as a source of family food, while fermented cassava peel waste has been utilized as feed for cattle, free-range chickens, and ducks. Through this initiative, KWT Indah Sari managed to reduce chemical fertilizer costs by 40%, and the use of cassava peel waste as feed has replaced 50% of forage for cows and 50% of corn in duck and chicken feed. In conclusion, integrated farming has proven effective in reducing production costs, thereby increasing household income.